Immigrant assimilation, trust and social capital - James C. Cox; Wafa Hakim Orman (Institute for the Study of Labor (IZA), 2010)
Trust is a crucial component of social capital. We use an experimental moonlighting game with a representative sample of the U.S. population, oversampling immigrants, to study trust, positive, and negative reciprocity between first-generation immigrants and native-born Americans as a measure of immigrant assimilation. We also survey subjects in order to relate trusting and trustworthy behavior with demographic characteristics and traditional, survey-based measures of social capital. We find that immigrants are as trusting as native-born U.S. citizens when faced with another native-born citizen, but do not trust other immigrants. Immigrants appear to be less trustworthy overall but this finding disappears when we control for demographic variables and the amount sent by the first mover. The length of time an immigrant has been a naturalized U.S. citizen appears to increase trustworthiness but does not affect trusting behavior. Women and older people are less likely to trust, but no more or less trustworthy.
Keywords: C93; J61; 330; moonlighting game; trust; reciprocity; immigration; experiment; Migranten; Soziale Integration; Bevölkerung; Vertrauen; Austauschtheorie (Soziologie); Spieltheorie; Test; USA